Development Of Interactive PowerPoint Media To Increase Students' Interest In Learning At MAN 3 Pekanbaru - Nurhidayati, Nurhidayati; Gimin, Gimin; Sumarno, Sumarno (Tadrib: Jurnal Pendidikan Agama Islam, 2023)
To make study guides easier for students to use both individually and in groups, this project attempts to turn PowerPoint into an interactive learning tool. It will keep students engaged and interested in what they are studying. This study employs a 4D model together with a development technique and development research strategy (R and D). Data gathering was carried out by 34 students and 1 instructor from XI Social Studies 2 MAN 3 Pekanbaru, as well as 2 media experts, 2 material experts, and users. Qualitative data were obtained from initial observations and interviews as well as assessments from validators; quantitative data were obtained from questionnaires of student responses and interest in learning shiva. A difference test with a paired sample t-test was used to examine the data using both qualitative and quantitative methodologies. PowerPoint interactive media is feasible to be tested, and student learning interest increases after limited trials are carried out. there is a notable gap between students' interests in learning before and after using interactive media from the results of various tests using matched samples. The t-test produced a significant result of 0.000 < 0.05, indicating that there is a substantial difference between the learning interests of the students before and after using the interactive PowerPoint media. The media is stated to be very practical and helpful, as evidenced by the student response percentage of 82.35%, which means that students respond that the level of practicality of media is high. The percentage of teacher responses of 100% shows that PowerPoint interactive media has high practicality and usefulness in the implementation of economic learning.